2019
DOI: 10.1109/tii.2019.2890849
|View full text |Cite
|
Sign up to set email alerts
|

Active Object Detection With Multistep Action Prediction Using Deep Q-Network

Abstract: In recent years, great success has been achieved in visual object detection, which is one of the fundamental tasks in the field of industrial intelligence. Most of existing methods have been proposed to deal with single well-captured still images, while in practical robotic applications, due to nuisances, such as tiny scale, partial view, or occlusion, one still image may not contain enough information for object detection. However, an intelligent robot has the capability to adjust its viewpoint to get better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…For example, in [15] it is demonstrated that developing a deep learning system that also predicts the next best move for a robot, using reinforcement learning, can significantly improve the performance of object detection, where the viewing angle, occlusions and the scale of each object can have a significant effect on the object recognition accuracy. Similar observations were also reported by more recent works [16], [17], [18]. At the same time, it is worth noting that active perception approaches often allow for developing faster and more lightweight DL models, since models are trained in order to solve a simpler problem.…”
Section: Introductionsupporting
confidence: 87%
“…For example, in [15] it is demonstrated that developing a deep learning system that also predicts the next best move for a robot, using reinforcement learning, can significantly improve the performance of object detection, where the viewing angle, occlusions and the scale of each object can have a significant effect on the object recognition accuracy. Similar observations were also reported by more recent works [16], [17], [18]. At the same time, it is worth noting that active perception approaches often allow for developing faster and more lightweight DL models, since models are trained in order to solve a simpler problem.…”
Section: Introductionsupporting
confidence: 87%
“…In recent years, the neural network-based methods have been widely applied in intelligent transportation systems [13][14][15], intelligent video surveillance [16,17], automatic monitoring [18,19], and industrial inspection [20,21] fields. By improving the Faster R-CNN network model, Sun et al realized the detection of scratch, oil pollution, block, and grinning four kinds of wheel hub defects quickly and accurately [22].…”
Section: Application Of the Industrial Inspection Based On Dcnnsmentioning
confidence: 99%
“…In [72], authors propose a novel fault diagnosis method for complex circuit board design using feed forward neural networks and support-vector machines that learns from repair history and localizes the root cause of a failure. In [73], X. Han et al formulate active object detection in industrial settings as a sequential action decision process, and apply a deep reinforcement learning framework, the deep Q-network (DQN) with dueling architecture to solve this formulation, by learning an optimal action policy. A deep neural network based two-stage automated approach for estimating the remaining useful life (RUL) of bearings in industrial machinery is proposed in [74], and in [75], authors model disassembly sequence planning as an NP-hard (non-deterministic polynomial-time hardness) many-objective problem, and solve this using the tensorial memetic algorithm that combines genetic computations with local search.…”
Section: Manufacturing Factories and Buildingsmentioning
confidence: 99%